Alterations in adipocytokines and cGMP homeostasis in morbid obesity patients reverse after bariatric surgery123. (26th March 2013) - Felipo, Vicente; Urios, Amparo; García‐Torres, Maria L.; El Mlili, Nisrin; del Olmo, Juan A.; Civera, Miguel; Ortega, Joaquin; Ferrandez, Antonio; Martínez‐Valls, Jose; Cassinello, Norberto; Montoliu, Carmina
Abstract: Objective: Obesity‐associated nonalcoholic fatty liver disease (NAFLD), covering from simple steatosis to nonalcoholic steatohepatitis (NASH), is a common cause of chronic liver disease. Aberrant production of adipocytokines seems to play a main role in most obesity‐associated disorders. Changes in adipocytokines in obesity could be mediated by alterations in cyclic GMP (cGMP) homeostasis. The aims of this work were: (1) to study the role of altered cGMP homeostasis in altered adipocytokines in morbid obesity, (2) to assess whether these alterations are different in simple steatosis or NASH, and (3) to assess whether these changes reverse in obese patients after bariatric surgery. Design and Methods: In 47 patients with morbid obesity and 45 control subjects, the levels in blood of adipocytokines, cGMP, nitric oxide (NO) metabolites, and atrial natriuretic peptide (ANP) were studied. Whether weight loss after a bariatric surgery reverses the changes in these parameters was evaluated. Results: NO metabolites and leptin increase (and adiponectin decreases) similarly in patients with steatosis or NASH, suggesting that these changes are due to morbid obesity and not to liver disease. Inflammation and cGMP homeostasis are affected both by morbid obesity and by liver disease. The increases in interleukin 6 (IL‐6), interleukin 18 (IL‐18), plasma cGMP, ANP, and the decrease in cGMP in lymphocytes are stronger in patients with NASH than with steatosis. All these changes reverse completely after bariatric surgery and weight loss, except IL‐18. Conclusion: Altered cGMP homeostasis seems to contribute more than inflammation to changes in leptin and adiponectin in morbid obesity.